ภูมิหลังและบทบาทสมาชิกสภาผู้แทนราษฎรสตรี : ศึกษากรณีเลือกตั้ง 17 พฤศจิกายน 2539 - ชัยนรงค์ วงศ์ใหญ่ (จุฬาลงกรณ์มหาวิทยาลัย, 1998)
The purpose of this thesis is to generalize the activity of female members of the House of Representatives in Thai politics. The study is to find the factors influencing the success in the election of female candidates and their roles as members of the House of Representatives. The study was conducted during the period of 3 November 1998 - 9 April 1999 by interviewing 14 female members of the House of Representatives in the November 17th general election. The study revealed that there were five major factors attributable to the success of those female candidates in the election, ranking by its importance, as follows: - 1) Personal profile (i.e. ag e, profession, education, economic and social status) 2) Patronage providing to the electoral community (money, material and etc.) 3) Creditability of political party including their campaigns and policies. 4) The influence and creditability of her father and mother 5) The influence and credit ability of the political party s leader. It was also found that most female members of the House of Representtatives were likely to take their roles outside the House of Representative, in other words, they tended to participate more on the community activities in order to have a continued support from voter for the next election. For the role taken on women s rights, the study showed that most of female members of the House of Representatives used their social role to solve the issues in women s rights.